PEMANFAATAN WEBSITE DESA DALAM MENINGKATKAN PELAYANAN PUBLIK MASA PANDEMI COVID-19 DESA CARAWALI - Sri Rachmayani Mursalim; Herman Dema; Abdul Jabbar (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
This study aims to find out how to use village websites in Carawali Village, Watang Pulu District, the use of village websites to improve public services during the COVID-19 pandemic in Carawali Village, Watang Pulu District. And the factors that influence the use of the website in Carawali Village, Watang Pulu District. The population in the study was 540 people and the sample was 54. This type of research is quantitative narrative. Data collection techniques mean observation, questionnaires (questionnaire) & literature. The analysis technique uses descriptive statistics. The results of the research output on the use of village websites in Carawali Village obtained poor results with an average percentage of 38.2%. The factors that encourage influencing E-Government are in the influential category with an average percentage of 70.9%. Then the use of village websites to improve public services during the COVID-19 pandemic shows a significant level of 0.002.